A clínica da subversão: considerações sobre a psicose e o tratamento psicanalítico pela via da transferência - Póvoa, Michelle Sousa (Universidade Federal do Tocantins, 2022)
This work is a conceptual theoretical study in the field of psychoanalysis that seeks to investigate the contributions and advances of psychoanalytic theory in psychosis studies, aiming to understand if it is possible to establish a transference relationship with psychotic patients and, in view of this, to glimpse the perspectives and consequences of a treatment that takes place through the clinical device of psychoanalysis. Psychosis, taken here from Freud, is understood as a personality structure arising from a powerful defense in which the self completely rejects an incompatible idea along with its affect. Based on his studies and clinical experiences, Freud makes a fundamental distinction between neurotic and psychotic structures, presenting extremely important theoretical elements. Throughout his work, the author addresses valuable questions about psychosis and the (im)possibilities of its psychoanalytic treatment, even contraindicating it for psychotic patients. It points out a difficulty related to the establishment of the transference link of these patients with the figure of the analyst, due to the particular characteristics of its mode of functioning, specifically due to the defense mode that structures it and its rejection to the external world due to a great libidinal disinvestment. It is from the continuity and deepening of studies on psychosis by the French psychoanalyst Jacques Lacan, in his return to Freud, that advances in understanding this structure and the possibilities of treatment emerge. Lacan presents us with a new understanding of psychosis, its constitution, the triggering and stabilization of a crisis in other ways. From Seminar 3 “The psychoses” (1955-1956), the author introduces important concepts to think about the peculiarities of the structure, such as “Foreclosure” and “Name-of-the-Father”, both closely associated, as foreclosure it is the result of the primordial rejection of a fundamental signifier that was not inscribed in the Symbolic register, and this, not being able to integrate with the subject's unconscious, returns to the Real. In this direction, Lacan conducts an investigation and theoretical and clinical path in the search to propose alternatives to the impossibility presented by Freud to the analytical treatment with psychotics. In his first clinic, he presents a path of treatment and stabilization through the construction of a "delusional metaphor" and repositions the analyst in the place of a "secretary of the alienated", that is, the one who will accompany the subject in his productions and assist in the construction of his metaphor, enabling him to build his own knowledge and meaning in existence.